Children’s critical evaluation of parental mediation - Leslie Haddon (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2015)
Although the new sociology of childhood draws attention to societal influences on children’s experiences, it also sees them as active agents. This article investigates children’s perspectives on parental interventions in regards their use of the internet, an aspect not covered in the parental mediation literature. Although children are generally positive about this mediation, here we explore cases where children consider it to be problematic through analysing the EU Kids Online qualitative research conducted in nine countries. The material shows how parental advice can sometimes be less articulated, justified, and expressed in a sensitive manner, and why it sometimes lacks credibility in children’s eyes. The article illustrates how maturing children can develop a sense of social expectations about independence, trust and personal social space. This can have a bearing on how they evaluate parental monitoring. Lastly, the article examines factors inhibiting children’s willingness to confide in parents about sensitive issues, because of potential parental responses, parenting styles, and a fear of losing parental trust that children have gained as they have grown older.